Vaccinia virus thymidine kinase and neighboring genes: mRNAs and polypeptides of wild-type virus and putative nonsense mutants. - Bajszár, G (1983)
Enzymatically active thymidine kinase (TK) was made in reticulocyte lysates programmed with early vaccinia mRNA that hybridized to plasmid recombinants containing either of two adjacent small DNA subsegments of the viral HindIII-J fragment. The map position of an early polypeptide, with a molecular weight of 19,000 (19K), coincided precisely with that of the TK. The absence of the 19K polypeptide in cell-free translation products of hybridization-selected mRNAs from several TK-negative mutants provided an independent identification of the TK polypeptide. The small size of the TK polypeptide of vaccinia virus distinguishes it from that of procaryotes, eucaryotes, and herpesvirus. Five early mRNAs of 3,840, 2,390, 1,790, 1,070, and 590 nucleotides were mapped within the HindIII-J fragment by RNA blotting and nuclease S1 digestion of RNA-DNA hybrids. The RNAs of 590 and 2,380 nucleotides were found to have 5' coterminal ends and represent major and minor forms, respectively, of the TK message. The 3' end of the minor TK mRNA appeared to be coterminal with the 3' end of the 1,790-nucleotide transcript which encodes a 41K polypeptide. The 1,070-nucleotide RNA was identified as the message for a 21K polypeptide. All of these RNAs, including the two forms of the TK message, were made by the putative TK-negative nonsense mutants.